Foreign accents Chinese American verse from exclusion to postethnicity - Yao, Steven G., 1965- (Global Asias., 2011)
This book undertakes linguistically informed analyses to examine the various transpacific signifying strategies by which different poets of Chinese descent in the United States have sought to employ or represent elements of a particular cultural tradition in their articulations of an ethnic subjectivity, including writings entirely in Chinese.